UMP language teachers won three gold medals and a silver medal at INNOPLEN 2019 - UMP, PNC; Juwairiah, Osman (2019)
The hard work put into developing innovative teaching techniques paid off for four language teachers with Universiti Malaysia Pahang (UMP)’s Centre for Modern Languages & Human Sciences (CMLHS) as they won three gold medals and one silver medal in the Innovation, Product Launching and Entrepreneurship (INNOPLEN) 2019 Competition.